Visibility of documentary heritage through digitisation projects in Romanian libraries - Micle, Maria; Tîrziman, Elena; Repanovici, Angela (Public Library of Science (PLoS), 2023)
Background The article presents, from a diachronic perspective, the concerns of valorization and preservation of the documentary heritage through digitisation projects in the Romanian Library System. The development of the argument is made starting from the analysis of the interest in the subject in international literature (through a bibliometric analysis) and the investigation of the online presence of libraries expressed statistically from the typology of forms of representation, to specific digital products and services, thus highlighting how they evolved in the sense of diversifying and modernizing the products and services provided and taking into account the political, economic, and technological constraints. Methods The evaluation of the involvement of Romanian libraries in digitisation activities was done through the such research methods as content analysis and scientometric research, which allowed the carrying out of a longitudinal case study extended for the period 2007–2022, during the unravelling of the events. Results The most representative initiatives for the creation of the Digital Library of Romania and the involvement of libraries in national and European projects are presented, and examples of good practices are highlighted, including political and administrative concerns to support protection and capitalization through the digitisation of the libraries’ heritage. This study is the first in Romanian specialized bibliography that proovides an overall and evolutionary perspective on the national project of digitisation of the documentary cultural heritage. Analyzing a large number of official documents and library web addresses has been a major challenge. Conclusions During the analyzed period (2007–2022), there have been numerous initiatives and digitisation projects, but the results have not always met expectations. From the experience of Romanian libraries, it can be concluded that digital content development initiatives have not always been successful because of the absence or insufficient commitment of the sustainability component.